SINTESIS DAN KARAKTERISASI NANOPARTIKEL KITOSAN – EKSTRAK KULIT BUAH MANGGIS (Garcinia Mangostana) - rismana, eriawan; Kusumaningrum, susi; p, olivia bunga; rosidah, idah; marhamah, marhamah (Jurnal Sains dan Teknologi Indonesia, 2012)
The chitosan – Garcinia Mangostana extract nanoparticles has been prepared by ionic gelation reaction by mixture 0.2 % chitosan solution in acetic acid with Garcinia Mangostana extract and it’s continued by reaction process with 0.1 % sodium tripolyphosphate. The particle size of material was determined by Particle Size Analyzer (PSA) that it showed in the range of 200 – 500 nm. The color, pH, water, α- mangostin, mercury, arsenic, cadmium, lead, totally microbe aerobic, totally mold and yeast, and solvent residue contents of nanoparticles were also examined by many methods that these resulted are yellow, 4.50 – 5.50, 89 – 90 %, 1.05 %, < 0.005 ppm, < 0.01 ppm, < 0.01 ppm, < 0.05 ppm, < 10 CFU/g, < 10 CFU/g and not detected, respectively. The other characterization was also observed that it’sincluded stability andTLC chromatogram. A mixture of nanoparticles with cosmetics bases was showed that it’s increased stability, homogeneity and easy to formed.